Gastrochilus kadooriei (Orchidaceae), a new species from Hong Kong, with notes on allied taxa in section Microphyllae found in the region. - Kumar, Pankaj; Gale, Stephan W.; Kocyan, Alexander; Fischer, Gunter A.; Averyanov, Leonid; Borosova, Renata; Bhattacharjee, Avishek; Li, Ji-Hong; Pang, Kuen Shum (Phytotaxa, 2014)
A new species, Gastrochilus kadooriei, is described from Hong Kong. Notes are presented on its distribution, ecology and conservation status, and its distinguishing features are compared with those of allied taxa. Gastrochilus jeitouensis is reduced to the synonymy of G. distichus, and a lectotype is assigned for G. pseudodistichus. Gastrochilus fuscopunctatus is reinstated as an accepted species. Dichotomous keys to this taxonomically difficult group of morphologically similar species are presented.